Incidence of Revenue generated by the Sale of drugs on Overall Hospital Revenue, case of the Kabondo General Reference Hospital in Kisangani (DRC) - Raymond ASSANI RAMAZANI; Bwanandeke Tshite Colette (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
The study looked at the impact of revenue generated by the sale of drugs on the overall revenue of a public hospital, the case of the Kabondo General Reference Hospital from 2018 to 2020. The objectives were to determine the sources of financing of the Kabondo General Reference Hospital and to identify the impact of revenue generated by the sale of medicines on the overall revenue of this health establishment. We opted for an inductive approach based on documentary analysis and supported by the linear correlation technique, which essentially concerned the hospital's overall revenue, from which we identified the impact of revenue generated by the sale of drugs. The main sources of funding for the Kabondo General Reference Hospital include: medical services (US227,006.47), sale of drugs (US68,323.04), operating subsidy (US56,358.40) and other income (US22,584.92). The revenue impact of drug sales at Kabondo General Referral Hospital from 2018 to 2020 is 18.3%. The financing of the hospital is either internal or external and the functioning of the Kabondo General Reference Hospital depends mainly on internal financing, as state subsidies and partner support are not significant. The sale of medicines is the second source of internal funding for the hospital.